Innovation of Student Talent Program at MTs Negeri 1 Langkat - Sindi Pertamasari; Nur Aini; Rosalinda Rosalinda; Intan Amalia; Rika Anggraini; Sartika Hutasuhut (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of students' potential, interests, and talents is an important part of realizing a holistic and adaptive education to the needs of the times. MTsN 1 Langkat as one of the leading state madrasas in North Sumatra has developed various innovative programs in the extracurricular field as a form of implementation of student talent development. This research aims to explore the forms of talent program innovation implemented, the implementation mechanism, as well as the outputs, outcomes, and impacts caused on student development. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The results of the study show that the talent program managed by OSIM and guided by competent teachers covers the fields of art, sports, religion, language, and academic olympics. This program has a positive impact on improving student discipline, confidence, and achievement, as well as strengthening the image of madrasah in the eyes of the public. However, weaknesses were found in the evaluation system that still focused on quantitative indicators, so it is necessary to develop an instrument that is able to measure qualitative aspects comprehensively. This study recommends the importance of character-based evaluation and potential in the sustainability of madrasah talent programs.